Authentic leadership through the theory of administrative excellence among academic leaders in Private Jordanian universities from the viewpoint of faculty members - يمنى عتوم; حسين عتوم; أسامة حسونة; محمد المقابلة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study aimed to identify the degree of practice authentic leadership through the theory of administrative excellence among academic leaders in Private Jordanian universities from the viewpoint of faculty members .The descriptive survey approach was used through the development of a questionnaire consisting of (27) items distributed to four areas: internal moral perspective, balanced treatment, transparency of relationships, and self-awareness, after its validity and reliability have been confirmed, the study sample consisted of (255) members chosen by the simple random method. The results of the questions showed that the degree of practicing authentic leadership through the theory of administrative excellence among academic leaders was moderate and showed that there were statistically significant differences at the significance level (α=0.05) between the arithmetic averages of the degree of practicing authoritative leadership through the theory of administrative excellence on the variable (sex, academic rank, number of years of experience, college). The study recommended raising awareness of the concept of authoritative leadership through holding training courses.